Classroom and territory. A study on heritage education - Selma Castell, Sergi; Lloría Adanero, Reis (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This research project falls within the conceptual framework of heritage education. The study aims to shed light on the theoretical and conceptual perceptions of heritage in education, but also the practices and didactic materials and the way they are used by different groups and agents involved in these teaching and learning processes. The research covers both formal and non-formal educational interventions and the way they open up school students and the general population to the cultural and educational values inherent in heritage assets.